2015
DOI: 10.1186/s11671-015-1016-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spectroscopy and Red Emission from β-Ga2O3/β-Ga2S3 Nanowires

Abstract: Ultrafast pump-probe and transient photoluminescence spectroscopy were used to investigate carrier dynamics in β-Ga 2 O 3 nanowires converted to β-Ga 2 O 3 /Ga 2 S 3 under H 2 S between 400 to 600°C. The β-Ga 2 O 3 nanowires exhibited broad blue emission with a lifetime of 2.4 ns which was strongly suppressed after processing at 500-600°C giving rise to red emission centered at 680 nm with a lifetime of 19 μs. Differential absorption spectroscopy reveals that state filling occurs in states located below the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Long carrier lifetime avoids immediate recombination of electrons and holes, hence, provides generation of large photocurrent. In contrast, the carrier lifetime and recombination process for UV-compatible Ga 2 O 3 is in the range of a few nanoseconds (2.4 ns [25]). In this regime, noticeably short transition time is necessary to overcome the immediate recombination of the carriers.…”
Section: Results and Disussionmentioning
confidence: 93%
“…Long carrier lifetime avoids immediate recombination of electrons and holes, hence, provides generation of large photocurrent. In contrast, the carrier lifetime and recombination process for UV-compatible Ga 2 O 3 is in the range of a few nanoseconds (2.4 ns [25]). In this regime, noticeably short transition time is necessary to overcome the immediate recombination of the carriers.…”
Section: Results and Disussionmentioning
confidence: 93%
“…20 The synthesis of a 0 -Ga 2 S 3 NWs has been demonstrated using various methods, including chemical vapor deposition (CVD) and sulfurization of Ga 2 O 3 NWs pre-synthesized by CVD or hydrothermal reaction. [21][22][23][24][25] The Sutter group synthesized g-Ga 2 S 3 nanotubes by sulfurization of GaAs NWs. 26 Since graphene-like two-dimensional (2D) layered materials have attracted much attention, the existence of 2D hexagonal crystal structures of Ga 2 S 3 was theoretically predicted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ga 2 S 3 , having a direct bandgap of ∼3.4 eV, exhibits high secondary-harmonic-generation efficiency and large laser-induced-damage threshold as well. [7][8][9][10][11][12][13] These characteristics make M 2 E 3 potential candidates for applications in optical switching devices, photovoltaic, and high power and/or high efficiency nonlinear optics. [11][12][13][14] One of the most important issues is to grow the group-III chalcogenide thin films with controllable crystal structures that can be compatibly integrated with mature semiconductor and/or optical devices.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13] These characteristics make M 2 E 3 potential candidates for applications in optical switching devices, photovoltaic, and high power and/or high efficiency nonlinear optics. [11][12][13][14] One of the most important issues is to grow the group-III chalcogenide thin films with controllable crystal structures that can be compatibly integrated with mature semiconductor and/or optical devices. 4,5,[10][11][12][13][14] Our recent studies revealed that Ga 2 S 3 thin films can be epitaxially synthesized on epiready GaAs (111) substrates via thermal vapor sulfurizations (TVS), however, their phase structures are strongly depended on the sulfurization conditions and durations.…”
mentioning
confidence: 99%
See 1 more Smart Citation